2011
DOI: 10.1682/jrrd.2010.03.0039
|View full text |Cite
|
Sign up to set email alerts
|

Telerehabilitation assessment using the Functioning Everyday with a Wheelchair-Capacity instrument

Abstract: Abstract-This study explored the interrater reliability between a generalist practitioner administering the Functioning Everyday with a Wheelchair-Capacity (FEW-C) in person (IP) and a remote expert practitioner observing via telerehabilitation (TR) from more than 100 miles away. Each of the 46 participants was simultaneously rated by both the IP and TR practitioner, who were masked to each other's results. The IP-TR raters demonstrated excellent interrater reliability, with an intraclass correlation coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Studies demonstrating the validity and reliability of this system have been performed to examine physical outcome measurements [6,10], observational kinematic gait analysis [11], upper-limb range of motion in stroke patients [12], lowerlimb range of motion in an orthopedic population [13], the effectiveness of rehabilitation following total knee replacement surgery [14][15][16], and diagnostic accuracy of ankle injuries [17]. Other studies using similar videoconferencing equipment have demonstrated that telerehabilitation assessments of Functional Reach, the European Stroke Scale, and the Functioning Everyday with a Wheelchair-Capacity can be performed accurately compared with face-to-face encounters [18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Studies demonstrating the validity and reliability of this system have been performed to examine physical outcome measurements [6,10], observational kinematic gait analysis [11], upper-limb range of motion in stroke patients [12], lowerlimb range of motion in an orthopedic population [13], the effectiveness of rehabilitation following total knee replacement surgery [14][15][16], and diagnostic accuracy of ankle injuries [17]. Other studies using similar videoconferencing equipment have demonstrated that telerehabilitation assessments of Functional Reach, the European Stroke Scale, and the Functioning Everyday with a Wheelchair-Capacity can be performed accurately compared with face-to-face encounters [18][19].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Schein et al on the interrater reliability between in-person and TR assessment of Functioning Everyday with a Wheelchair-Capacity demonstrated excellent results, with an interclass correlation coefficient of 0.91, although the system was tested under high-bandwidth conditions [14]. In a separate study, Schein et al again compared TR sessions on wheeled mobility and seating assessments with in-person assessment scenarios and the results indicated that the TR sessions were equally effective as the "gold standard" inperson assessments [2].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The traditional telephone system continues to be a low-cost alternative for effectively conducting interview assessments by various health care professionals (Cooper et al, 2002;Dreyer, Dreyer, Shaw, & Wittman, 2001;Winters, 2002), and advanced communication technologies have broadened the possibilities for conducting evaluations. Studies have described the use of telehealth in areas that are of concern to occupational therapy, such as evaluation and consultative services for wheelchair prescription (Barlow, Liu, & Sekulic, 2009;Schein, Schmeler, Brienza, Saptono, & Parmanto, 2008;Schein, Schmeler, Holm, Saptono, & Brienza, 2010;Schein et al, 2011), neurological assessment (Savard, Borstad, Tkachuck, Lauderdale, & Conroy, 2003), adaptive equipment prescription and home modification (Sanford et al, 2007), and ergonomic assessment (Baker & Jacobs, 2013).…”
Section: Evaluation Using Telehealth Technologies: Tele-evaluationmentioning
confidence: 99%